2021
DOI: 10.48550/arxiv.2104.14361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anisotropic Triebel-Lizorkin spaces and wavelet coefficient decay over one-parameter dilation groups, I

Abstract: This paper provides maximal function characterizations of anisotropic Triebel-Lizorkin spaces associated to general expansive matrices for the full range of parameters p ∈ (0, ∞), q ∈ (0, ∞] and α ∈ R. The equivalent norm is defined in terms of the decay of wavelet coefficients, quantified by a Peetre-type space over a one-parameter dilation group. For the Banach space regime p, q ≥ 1, we use this characterization to prove the existence of frames and Riesz sequences of dual molecules for the Triebel-Lizorkin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(48 citation statements)
references
References 46 publications
1
47
0
Order By: Relevance
“…In a previous paper [20], we obtained characterizations of anisotropic Triebel-Lizorkin spaces Ḟα p,q , with α ∈ R, p ∈ (0, ∞) and q ∈ (0, ∞], in terms of Peetre-type maximal functions and continuous wavelet transforms. In addition, as an application of these characterizations, it was shown that these spaces admit dual frames and Riesz sequences of molecules.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous paper [20], we obtained characterizations of anisotropic Triebel-Lizorkin spaces Ḟα p,q , with α ∈ R, p ∈ (0, ∞) and q ∈ (0, ∞], in terms of Peetre-type maximal functions and continuous wavelet transforms. In addition, as an application of these characterizations, it was shown that these spaces admit dual frames and Riesz sequences of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the usual quasi-norms defining (anisotropic) Triebel-Lizorkin spaces Ḟα p,q for p < ∞ (see, e.g., [3][4][5]20]), the quantities (1.3) and (1.4) consider only averages over small scales. The quasi-norms (1.3) and (1.4) can therefore be considered as "localized versions" of the immediate analogue of the quasi-norms defining Ḟα p,q for p < ∞, which would lead to an unsatisfactory definition of Ḟα ∞,q , see [11,Section 5] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations